UMPSA continues to excel in MS ISO 9001:2015 Quality Management System (QMS) Surveillance Audit by SIRIM QAS International - Hazlina, Faizal (UMPSA, 2025)
PEKAN, 26 September 2025 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) has completed the MS ISO 9001:2015 Surveillance Audit conducted by SIRIM QAS International recently.